Factors influencing safe glucose-lowering in older adults with type 2 diabetes: A PeRsOn-centred ApproaCh To IndiVidualisEd (PROACTIVE) Glycemic Goals for older people: A position statement of Primary Care Diabetes Europe. Issue 4 (August 2019) - Hambling, C.E.; Khunti, K.; Cos, X.; Wens, J.; Martinez, L.; Topsever, P.; Del Prato, S.; Sinclair, A.; Schernthaner, G.; Rutten, G.; Seidu, S.
Highlights: Diabetes in later life poses challenges, due to a range of interrelated factors. Holistic person-centred care is advocated to promote general health and wellbeing. A comprehensive, holistic approach aids PROACTIVE individualised glycaemic goals. Avoiding uncontrolled hyperglycaemia and hypoglycaemia may reduce adverse outcomes. Decision algorithms offer clinical support for glycaemic management in older people. Abstract: Diabetes in later life is associated with a range of factors increasing the complexity of glycaemic management. This position statement, developed from an extensive literature review of the subject area, represents a consensus opinion of primary care clinicians and diabetes specialists. It highlights many challenges facing older people living with type 2 diabetes and aims to support primary care clinicians in advocating a comprehensive, holistic approach. It emphasises the importance of the wishes of the individual and their carers when determining glycaemic goals, as well as the need to balance intended benefits of treatment against the risk of adverse treatment effects. Its ultimate aim is to promote consistent high-quality care for older people with diabetes.